PENERAPAN SISTEM KEUANGAN DESA (SISKEUDES) PADA ORGANISASI PEMERINTAHAN DESA (STUDI KASUS DI DESA SUWAAN KECAMATAN KALAWAT KABUPATEN MINAHASA UTARA) - Malahika, Jehan M.; Karamoy, Herman; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This research aims to analyze the Implementation of Village Financial System (SISKEUDES)Â towards the government organization in Suwaan Village Kalawat Subdistrict North Minahasa Regency. This research using qualitative research approach as using primary data, which were in the form of interview and secondary data. The informants are the village head, the village secretaries, and the head of village government affairs. The result showed that : (1) The implementation of Village Financial System in Suwaan Village has running well (2) The procedure of SISKEUDES utilization done by 4 stages which are : Planning, Implementing, Administrating, and Reporting (3) Village Financial System has been giving the positive influence towards the performance of each employee. Therefore, Village Financial System holds an important role upon village government that impact directly by the employee of village. This is as accordance with the purpose on the implementation of Village Financing System which is to assist the work of villagersâ€™ employee. Keywords: Village Financial System, Village Government